(untitled) (World Bulletin of Public Health, 2023)
Establishment of the optimal norms of mineral fertilizers against the background of the introduction of organic fertilizers (manure) for the Polovchanka wheat variety under the conditions of old irrigation of light gray soils and the rationale for their positive effect on growth, development, crop, damage. The main goal of the research is to solve the influence of the quality of the regime on the technological indicators that show the quality of the Polovchanka grain, a variety of winter wheat, under conditions of light gray soil in the Kashkadarya region